The Relation between Accounting Conservatism and Corporate Social Performance: An Empirical Investigation. (3rd June 2013) - Francis, Rick N.; Harrast, Steven; Mattingly, James; Olsen, Lori
Abstract Accounting conservatism and corporate social responsibility have received much attention in the recent literature. The current study draws upon Watts, who recognizes that one role of conservatism is to reduce the likelihood of excess wealth transfers to its stakeholder groups and Post et al., who assert that a key aspect of positive corporate social performance is the (equitable) distribution of corporate wealth. Accordingly, this study empirically investigates and finds a positive relation between conservatism and strong social performance.